2011
DOI: 10.3892/etm.2011.383
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib has better efficacy than gefitinib in adenocarcinoma patients without EGFR-activating mutations, but similar efficacy in patients with EGFR-activating mutations

Abstract: Abstract. Epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) are an effective treatment for advanced non-small cell lung cancer. The objective of the present study was to compare the efficacy of gefitinib and erlotinib in patients with pulmonary adenocarcinoma, whose tumor EGFR mutation status was known. Pulmonary adenocarcinoma patients who began receiving gefitinib or erlotinib treatment from January 2005 to December 2010, and whose tumor EGFR mutation status had been determined, were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In addition to these studies, several retrospective registry studies showed similar efficacy of gefitinib and erlotinib in patients with advanced/metastatic or recurrent NSCLC [92,93] or stage IIIB or IV pulmonary adenocarcinoma [94]. Furthermore, a recent network meta-analysis indirectly compared the efficacy of gefitinib, erlotinib, icotinib and afatinib and showed that the four agents had generally similar efficacy in patients with NSCLC and activating EGFR mutations [95].…”
Section: Dosage and Administrationmentioning
confidence: 96%
“…In addition to these studies, several retrospective registry studies showed similar efficacy of gefitinib and erlotinib in patients with advanced/metastatic or recurrent NSCLC [92,93] or stage IIIB or IV pulmonary adenocarcinoma [94]. Furthermore, a recent network meta-analysis indirectly compared the efficacy of gefitinib, erlotinib, icotinib and afatinib and showed that the four agents had generally similar efficacy in patients with NSCLC and activating EGFR mutations [95].…”
Section: Dosage and Administrationmentioning
confidence: 96%
“…This study included 224 patients, with known tumour EGFR mutation status, who had received TKI treatment (124 gefitinib and 100 erlotinib) but was not restricted to first-line treatment; no significant difference between the two treatments was observed for either PFs or OR rate. 77 …”
Section: Clinical Effectivenessmentioning
confidence: 99%
“…More treatment-related grade-3 or -4 adverse events were observed with erlotinib versus gefitinib (12.4% vs 4.2%). Wu et al 10 conducted a retrospective study to evaluate the difference in efficacy between erlotinib and gefitinib in Taiwanese patients with advanced-stage EGFR mutation-positive NSCLC. They also found no statistically significant difference in response rate and PFS between the two drugs.…”
Section: Comparison Is Beyond Ipass and Optimalmentioning
confidence: 99%